On the stability with probability one for a class of stochastic semigroups - Chani, A.C. (Інститут математики НАН України, 2005)
The formulated theorem speciﬁes the result of A.V. Skorokhod concerning the stability
with probability one for the solution of a linear stochastic system built on a
continuous homogeneous semimartingale with independent increments.